Factorise Completely: 3x2y + 11xy + 6y - Mathematics

Advertisement Remove all ads
Sum

Factorise completely: 3x2y + 11xy + 6y 

Advertisement Remove all ads

Solution

3x2y + 11xy + 6y = y(3x2 + 11x + 6)

= y[(3x2 + 9x + 2x + 6)]

= y[3x (x + 3) + 2(x + 3)]

= y [(x + 3)(3x + 2)]

= y (x + 3)(3x + 2)

Concept: Factorising Completely
  Is there an error in this question or solution?

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 13 Factorisation
Exercise 13 (E) | Q 14 | Page 162
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×